2010
DOI: 10.1017/s0305000910000346
|View full text |Cite
|
Sign up to set email alerts
|

Lexical tone awareness among Chinese children with developmental dyslexia*

Abstract: This study examined the extent and nature of lexical tone deficit in Chinese developmental dyslexia. Twenty Cantonese-speaking Chinese dyslexic children (mean age 8;11) were compared to twenty average readers of the same age (CA control group, mean age 8;11), and another twenty younger average readers of the same word reading level (RL control group, mean age 7;4) on different measures of lexical tone awareness, rhyme awareness and visual-verbal paired-associate learning. Results showed that the Chinese dyslex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 29 publications
2
32
0
1
Order By: Relevance
“…Our study also indicates that tone awareness in grade 1 predict grade 2 character reading longitudinally, when other related skills and the autoregressor of grade 1 character reading are controlled strictly. This result confirms previous research findings (Li & Ho, 2011;Siok & Fletcher, 2001) and suggests that tone awareness is an important linguistic skill in the initial years of learning to read. A previous study (Ho & Bryant, 1997a) suggested that rime awareness assessed with tone at the age of 4 longitudinally predicted character reading at 7 years old (grade 1).…”
Section: The Prediction Of Phonological Awareness For Character Readisupporting
confidence: 92%
“…Our study also indicates that tone awareness in grade 1 predict grade 2 character reading longitudinally, when other related skills and the autoregressor of grade 1 character reading are controlled strictly. This result confirms previous research findings (Li & Ho, 2011;Siok & Fletcher, 2001) and suggests that tone awareness is an important linguistic skill in the initial years of learning to read. A previous study (Ho & Bryant, 1997a) suggested that rime awareness assessed with tone at the age of 4 longitudinally predicted character reading at 7 years old (grade 1).…”
Section: The Prediction Of Phonological Awareness For Character Readisupporting
confidence: 92%
“…4 Reduced lexical tone awareness has frequently been reported among Chinese-speaking children with dyslexia. 5,6 Chinese Mandarin has four lexical tones, each with a different internal pattern of rising and falling pitch, that is, a change of fundamental frequency. Because frequency modulation (FM) is one of the most vital physical aspects of making lexical distinctions, a neurophysiological investigation of the sensitivity of the human auditory system to FM signals may help elucidate the processing difficulties of lexical tones in Chinese-speaking children.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that orthographic skills and rapid naming were associated with dyslexia; phonological memory and morphological awareness were associated with SLI; and phonological awareness was associated with both. In other studies of lexical tone awareness, both children with DD [35] and children with SLI [36] were found to be weak in tone discrimination and production (a unique phonological feature of the Chinese language). Findings of these studies together appear to show that orthographic deficit and rapid naming deficit are unique marker deficits of DD in Chinese, but morphological or phonological deficit is probably not.…”
Section: Cognitive Profiles Of Reading and Spelling Difficulties In Cmentioning
confidence: 86%